2022
DOI: 10.1111/srt.13269
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy treats acne by altering the composition of the skin microbiota

Abstract: Background Acne is the eighth‐most prevalent inflammatory skin disease with no optimal treatment. Photodynamic therapy (PDT) is an effective treatment for severe acne. Aims The effect of PDT on the composition and diversity of skin microflora in severe acne patients was studied. Materials and Methods A total of 18 patients with severe acne and 8 healthy individuals were selected for this study. Patients were treated with 5‐aminolevulinic acid‐mediated PDT once a week three times in total; the skin microbiome w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…However, this bimodal procedure of ALA application and targeted light lends itself to increased considerations when assessing the cause of microbiome impacts. Two of the three studies showed a general increase in diversity after treatment, while Guo et al found a slight decrease in alpha diversity following treatment that decreased with subsequent treatments [44,45,61]. ALA-PDT treatment also led to the decrease of some bacteria implicated in skin diseases, such as C. acnes.…”
Section: Phototherapy Significantly Alters the Skin Microbiomementioning
confidence: 98%
See 1 more Smart Citation
“…However, this bimodal procedure of ALA application and targeted light lends itself to increased considerations when assessing the cause of microbiome impacts. Two of the three studies showed a general increase in diversity after treatment, while Guo et al found a slight decrease in alpha diversity following treatment that decreased with subsequent treatments [44,45,61]. ALA-PDT treatment also led to the decrease of some bacteria implicated in skin diseases, such as C. acnes.…”
Section: Phototherapy Significantly Alters the Skin Microbiomementioning
confidence: 98%
“…It includes several broad treatment types used throughout the reviewed studies-namely, UV phototherapy, light therapy, laser therapy, and photodynamic therapy [39]. It is generally associated with an increase in microbiome diversity [40][41][42][43][44][45][46][47]. However, some studies found no significant change in this regard [48,49].…”
Section: Phototherapy Significantly Alters the Skin Microbiomementioning
confidence: 99%
“…Additionally, doxycycline increased bacterial alpha-diversity in acne [ 33 ] Photodynamic therapy (PDT) Severe acne ALA-PDT treatment led to clinical improvements. Meanwhile, ALA-PDT treatment increased the diversity of skin microbiome, with decreased C. acnes abundance in severe acne [ 42 44 ] Retinoid NA Retinoid treatment improved the clinical acne grades, increased the alpha-diversity, and reduced the abundance of Propionibacterium , whereas increased the abundance of several other taxa, when compared with controls [ 47 ] Supramolecular salicylic acid (SSA) Moderate-to-severe The 30% SSA peels improved GAGS scores and skin barrier indicators, while decreased richness and evenness of cutaneous microbiome in acne patients [ 49 ] The 2% SSA treatment increased the clinical outcomes, as well as the α- and β-diversity index in acne patients. Specifically, the relative abundance of Staphylococcus , Ralstonia , and Streptococcus was significantly decreased by 2% SSA treatment, with overall bacteria genera distribution tends toward the healthy status [ 50 ] Myrtacine ® Global Acne Severity Scale, GEA grades 2–3 The Myrtacine ® -based cream improved acne lesions and reduced the level of erythromycin resistance C. acnes in acne patients, without changing the total C. acnes load [ 52 ] …”
Section: Therapeutic Interventions Change Skin Microbiota In Acne Pat...mentioning
confidence: 99%
“…Healthy individuals were simultaneously recruited to serve as controls. The baseline data revealed marked differences in microbiota composition between healthy controls and acne patients, characterized by reduced alpha-diversity in the patient cohort [ 42 ]. Intriguingly, ALA-PDT treatment resulted in noticeable modifications to the patients’ microbiota composition, including 15 bacterial genera, such as Enhydrobacter , Cetobacterium , and Streptococcus [ 42 ].…”
Section: Therapeutic Interventions Change Skin Microbiota In Acne Pat...mentioning
confidence: 99%
See 1 more Smart Citation